Episodic memory effects of gamma frequency precuneus transcranial magnetic stimulation in Alzheimer's disease: A randomized multiple baseline study - Traikapi, Artemis; Kalli, Ioanna; Kyriakou, Andrea; Stylianou, Elena; Symeou, Rafaella Tereza; Kardama, Akrivi; Christou, Yiolanda Panayiota; Phylactou, Phivos; Konstantinou, Nikos (My University, 2023)
Episodic memory decline is the prominent neuropsychological feature of typical Alzheimer's Disease (AD), for which current treatments have a limited clinical response. Recently, gamma entrainment therapy has been used as a non-invasive treatment in AD, providing evidence that it may have the potential to alleviate brain pathology and improve cognitive function in AD patients. At the same time, the precuneus (PC) has been recognized as a key area involved in AD related memory deficits and as a key node of the Default Mode Network. This study aimed to investigate the effectiveness of a 40 Hz Transcranial Magnetic Stimulation (TMS) intervention, delivered bilaterally to the precuneus for 10 days, in improving the patients' episodic memory performance. Secondary outcome variables investigated included general cognitive function, semantic and spatial memory, as well as attention and executive function. A concurrent multiple baseline design across five cases was employed. Four patients completed the study. Visual analysis combined with effect size indices were used to evaluate changes across phases. An increase in the average level of immediate recalled words was observed in three out of four patients. Effect size indices indicated significant improvement of attention skills in two patients. No treatment effect was observed for semantic and visual memory, or for executive function. An immediate treatment effect was observed in all patients' general cognitive function as assessed with the Alzheimer's Disease Assessment Scale (mean reduction of 5 points), which was maintained and improved further three months post-treatment. The neuropsychological evaluations indicated improved performance three months post-treatment in immediate and delayed recall, attention, phonological verbal fluency, anxiety, and neuropsychiatric symptoms. This study provides preliminary evidence for the efficacy of a novel non-pharmacological treatment using gamma-band TMS in addressing cognitive dysfunction in AD.
Keywords: Alzheimer's Disease; episodic memory; gamma frequency brain stimulation; precuneus; transcranial magnetic stimulation